My first animal board book - Zarick, Nicole; Lilly, Kenneth; DK Publishing, Inc. (New York DK Publishing, Inc., 1998)
A word book to help children identify different types of animals, featuring full-colour photographs and large, easy-to-read text to encourage early learning and vocabulary development.
On board pages. Originally published in 1998 by Dorling Kindersley as My little animals board book.
ages 1-5 Preschool
Keywords: Animals Vocabulary Board books